إشكالات الفصل والوصل بين المنهجية والمذهبية في الفكر الإسلامي: الإشكال المفهومي نموذجاً - سعاد كوريم (International Institute of Islamic Thought, 2014)
إنَّ تقييم إنتاجات الفكر الإسلامي وتقويمها رهين بتعيين حدود الوصل والفصل بين المنهجية والمذهبية. وتعترض طريق ذلك التعيين وتؤثر فيه جملة من الإشكالات، أبرزها الإشكال المفهومي النابع من عدم الدقة في تحديد معنيي المنهج والمذهب. يتخذ الإشكال المفهومي صوراً عديدة بعدد زوايا النظر إليها؛ أهمها الزاوية التي تدرس اللفظين بحسب حظيهما من خصيصتي الاتفاق والنضج المحددتين لمستوى الاصطلاح، وتبين أثر ذلك في توسيع أو تقليص إمكانات الوصل أو الفصل بينهما. هذه الزاوية هي التي يُعنى بها هذا البحث، ويستثمر في خدمتها بعض تعريفات المنهج والمذهب واستعمالاتهما، جامعاً في عمله بين التحليل والنقد. The evaluation of products of Islamic thought passes through the delimitation of the boundaries between methodology and doctrine. That delimitation encounters, and is influenced by, a series of problems, most notably the conceptual confusion caused by the lack of precision in the definition of the concepts. The confusion takes several forms depending on what perspective one sees it from. This paper focuses on the view that studies the words "methodology" and "doctrine" according to their terminological level, which is defined by the amount of their maturity and the level of agreement upon their meaning. It also shows the impact of the terminological level on extending or reducing the possibilities of connection or separation between methodology and the doctrine. For this purpose the author has critically analyzed some definitions and uses of the two concepts; namely, methodology and doctrine.